Management of chilli (Capsicum annuum) anthracnose using fungicides and biocontrol agents - R. VELAZHAHAN, V. PARANIDHARAN and M. KARTHIKEYAN, S. MADHAVAN, P. ADHIPATHI* (Indian Phytopathology, 2017)
An antagonistic Burkholderia sp. strain TNAU-1 and the fungicide, Cabrio Top were evaluated for their efficacy in suppressing mycelial growth of chilli anthracnose pathogen isolates of Colletotrichum capsici, C. gloeosporioides and Alternaria alternata in vitro. Antagonistic bacterium inhibited the growth of all the aforementioned pathogenic isolates in dual culture on PDA medium and the inhibition zone ranged from 10.7 mm (CBE1) to 16.0 mm (TEN10). The test fungicide Cabrio Top was highly effective in suppressing the radial growth of all the test fungi with minimal inhibitory concentration at 250 ppm. In the field trial, Cabrio Top at @ 1750 g/ ha was found to be most effective in controlling anthracnose and increasing yield. Control plots recorded the lowest yield of 2132 kg/ha and 2507 kg/ha in Trial I and Trial II, respectively. Cabrio Top @1750g/ha recorded the highest yield of 3091kg/ha and 3304 kg/ha in Trial-I and Trial-II, respectively. Foliar application of powder formulation of Burkholderia sp. strain TNAU-1 showed a comparable level of disease control and increased the yield to that of foliar application with Cabrio Top under field conditions.